2015
DOI: 10.1155/2015/465358
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of Continuous Carbon Nanotube Networks Modified Cf/SiC Composite

Abstract: Continuous carbon nanotube (CNT) networks were formed in Cf/SiC composites via freeze-drying method. Composites were fabricated by precursor infiltration and pyrolysis (PIP) process afterwards. The different distribution morphologies of CNTs in the preforms originating from the different CNT contents were analyzed while the influence of the distribution of CNTs was discussed in detail. Compared to composites without CNTs, the interfacial shear strength (ILSS) and the flexural strength of Cf/1%CNTs/SiC were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…To date, several attempts have been made to introduce CNTs into the C f /SiC composites with the aim of enhancing their mechanical parameters and thermal conductivity. For example, Yu et al [28] embedded commercial multi-walled CNTs (0.0765 wt%) as raw materials in 3D preform via slurry infiltration, and then obtained C f /SiC composites via precursor infiltration and pyrolysis (PIP) technique. The results showed that the flexural strength and room-temperature thermal conductivity of the composites doped with CNTs were 311.4 MPa and 1.81 W•m −1 •K −1 , respectively, exceeding those of the pristine materials by 25% and 30%.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several attempts have been made to introduce CNTs into the C f /SiC composites with the aim of enhancing their mechanical parameters and thermal conductivity. For example, Yu et al [28] embedded commercial multi-walled CNTs (0.0765 wt%) as raw materials in 3D preform via slurry infiltration, and then obtained C f /SiC composites via precursor infiltration and pyrolysis (PIP) technique. The results showed that the flexural strength and room-temperature thermal conductivity of the composites doped with CNTs were 311.4 MPa and 1.81 W•m −1 •K −1 , respectively, exceeding those of the pristine materials by 25% and 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber-reinforced silicon carbide (C f /SiC) ceramic matrix composites, one of the most famous CMCs, are becoming the most promising candidates for hightemperature structural applications (as illustrated in Figure 1), such as sharp leading edges, nose cones, aeronautic jet engines, thermal protection systems for reusable atmosphere reentry vehicles [12,13], as well as optical components [14] and nuclear fusion/fission reactors [15,16], owing to their relatively low density (∼2 g/cm 3 ), high thermal conductivity (∼67 W/(m·K)), high strength (300-800 MPa) [17][18][19], low coefficient of thermal expansion (CTE, 3.0-3.1 × 10 −6 ·K −1 ), especially good stability and excellent oxidation and creep resistance at elevated temperatures [13,[21][22][23]25]. In particular, C f /SiC composites have shown significant improvements in fracture toughness and thermal shock resistance.…”
Section: Introductionmentioning
confidence: 99%